Peranan ilmu ashwat dalam pengembangan ilmu teoritis - Udin, Ahmad Irfan (Maliki Interdisciplinary Journal, 2024)
In the study of Arabic linguistics imu ashwat has an important contribution to the development of linguistics. At the level of implementation of language studies, linguists (linguists) use several approaches. many use several approaches. These approaches that eventually became a designation or part of the linguistic branches themselves. And of that theoretical science is a branch of linguistics. In linguistic studies ashwat science is also called the science of sound which is the same as Ashwat science. Therefore we recognize the terms phonetics and phonology, which are divisions of the study of Ashwat. which is a division of the study of Ashwat or the science of sound. In linguistics, the science of Ashwat provides deep insight into the phonetic and phonological structure of the language, enabling the analysis of the phonological structure of the language. and phonological structure of the language, allowing a more accurate analysis of the differences and similarities between languages. differences and similarities between languages. In phonetics, it helps decipher the acoustic properties of the human voice, which plays an important role in the development of speech recognition and speech synthesis. In essence, language is a sound which becomes a study in the acquisition of the language, so that the root of the problem that lies in the acquisition of the language. study in the acquisition of the language, so that the root of the problem that is in the language can be concluded to be in the sound or in Arabic. language can be concluded to be in sound or in Arabic by the name of the science of Ashwat.